Correction: Progressive changes in crystallographic textures of biominerals generate functionally graded ceramics. Issue 5 (16th February 2022) - Wallis, David; Harris, Joe; Böhm, Corinna F.; Wang, Di; Zavattieri, Pablo; Feldner, Patrick; Merle, Benoit; Pipich, Vitaliy; Hurle, Katrin; Leupold, Simon; Hansen, Lars N.; Marin, Frédéric; et al.
Abstract : Correction for 'Progressive changes in crystallographic textures of biominerals generate functionally graded ceramics' by David Wallis et al., Mater. Adv., 2022, DOI: ; 10.1039/d1ma01031j .